INFLUENCE OF BABY MASSAGE KIT (BABY MASSAGE, MUSIC, AROMA THERAPY) ON BABY DEVELOPMENT at BIDAN'S PRIVATE PRACTICE IN PRUMNAS DISTRICT OF REJANG LEBONG DISTRICT - Puspita, Yenni; Esmianti, Farida (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Aspects of development are gross motor, fine motor, personal social, and language. child development problems such as motor delays. Developmental delays in children can be prevented by providing stimulation that can improve development in children. one form of stimulation is baby massage. This study aims to determine the effect of baby massage KIT (baby massage, music, aromaTherapy) on the development of toddlers in the independent practice of midwives in the working area of the health center prumnas rejang lebong Bengkulu.Quasi Experimental research design, with pre test and post test design with control group.The population in this study were all toddlers in the working area of Perumnas Health Center, Rejang lebong Regency, Bengkulu Province. The sample was toddlers in the work area of Perumnas Health Center, Rejang lebong Regency, Bengkulu Province. The sampling technique was purposive sampling. The number of samples in this study were 42 respondents, with the criteria of 21 respondents in each group. The data collection tool in this study used a questionnaire to determine the characteristics of the respondent's mother, development in toddlers. Data collection for development using KPSP instruments. The data analysis used was the Wilcoxon test and the man whitney test. The results showed the influence of baby massage KIT (baby massage, music, aroma therapy) on the development of toddlers with a value of P <0.05. Conclusion: There is an effect of baby massage KIT (baby massage, music, aromaTherapy) on the development of toddlers. man whitney test obtained p value 0.000 <0.05 this means there is a difference in influence between baby massage Kit and conventional massage counseling on development